Connection analysis of an x-zero-type helical gear pair - Bodzás, Sándor (International Journal of Engineering and Management Sciences, 2019)
We designed a helical gear pair, after we prepared the CAD models of the elements. Using of these models connection analysis will be done in case of the application of different torques. The established stress, strain and deformation values will be analysed on the connection tooth surfaces and the fillet radiuses in case of teeth connection.